Beauty and Influence: Understanding the Effects of Product Quality and Influencers on Brand Image and Consumer Choices - Annisa Putri, Siti; Annio Indah Lestari Nasution; Siti Aisyah (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Industry beauty has become Wrong One industry Which very competitive, in where various brand compete For interesting attention consumer Which the more intelligent And experienced, This research is important because it’s provides relevance in the context of consumer trends that increasingly prioritize sustainability and ethical values, which can strengthen long-term relationships between the brand and consumers. Objective in study This is For analyze influence quality products and the role of beauty influencers in purchasing decisions through brand image variables make over product case study. The novelty of this research lies in its focus on exploring the role of product quality and beauty influencers on purchase decisions through brand image, specifically for Make Over products, amid changing digital consumption trends. In this study, quantitative methods were used to analyze connection between variable. Sample Which used consists of from 96 person respondents were selected randomly. Data was collected through a questionnaire then analyzed data done use technique statistics For test hypothesis And determine significance of the influence between variables. The results of the study showed that Product Quality was proven has a significant positive influence on Brand Image and Purchase Decision. In On the other hand, Beauty Influencers also have a significant positive influence on Brand Image, but No influential significant to Purchase Decision. Brand Image Alone own significant positive influence on Purchase Decision. However, Brand Image does not mediates the influence of Product Quality on Purchase Decision, while Brand Image play a role as a moderator in Beauty Influencer influence to Purchase Decision.